2014
DOI: 10.4314/ajtcam.v11i3.33
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Genotype and Phylogenetic Groups in relation to Chinese Herb Resistance among <i>Escherichia Coli</i> from Patients with acute Pyelonephritis

Abstract: Background: Clinical isolates of herb-resistant uropathogenic E. coli were isolated. It was possible that the virulence genotypes and phylogenetic background of E. coli differed between Chinese herb-resistant E. coli and -susceptible isolates. For this purpose, the prevalence of virulence factors (VFs) and phylogenetic background, with regard to Chinese herb resistance, among E. coli strains causing acute pyelonephritis from China were investigated. Materials and Methods:E. coli isolates from patients with acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
3
3
1
Order By: Relevance
“…The other 41.13% could not be typed as ExPEC using this method, indicating that the predictive virulence genes score is not always sufficient for classification of ExPEC as has also been reported before (Berman et al, 2014 ). In general, ExPEC can be classified into five phylogenetic groups, i.e., A, B (subgroups B1 and B2), D, E, and F, and the majority of the isolates in our study belonged to phylogenetic groups B2 and D. Indeed, other studies, as the ones from Iran and China, show that human pathogenic ExPEC predominantly belong to these two groups (Kazemnia et al, 2014 ; Tong et al, 2014 ), that are also considered to be more virulent and more associated with infections than, e.g., phylogenetic groups A and B1 (Lee et al, 2016 ). In our study, two isolates could not be assigned to any of the phylogenetic groups.…”
Section: Discussionsupporting
confidence: 54%
“…The other 41.13% could not be typed as ExPEC using this method, indicating that the predictive virulence genes score is not always sufficient for classification of ExPEC as has also been reported before (Berman et al, 2014 ). In general, ExPEC can be classified into five phylogenetic groups, i.e., A, B (subgroups B1 and B2), D, E, and F, and the majority of the isolates in our study belonged to phylogenetic groups B2 and D. Indeed, other studies, as the ones from Iran and China, show that human pathogenic ExPEC predominantly belong to these two groups (Kazemnia et al, 2014 ; Tong et al, 2014 ), that are also considered to be more virulent and more associated with infections than, e.g., phylogenetic groups A and B1 (Lee et al, 2016 ). In our study, two isolates could not be assigned to any of the phylogenetic groups.…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with our study, a study from Egypt 35 has documented that phylogroup A is predominant in UPEC strains followed by group B2 and lastly D. The predominance of phylogroup A E. coli has been also reported in China, 39 Russia 40 and Iran. 41…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, phylogroup D was the most prevalent group causing UTI in China. 38 Consistent with our study, a study from Egypt 35 has documented that phylogroup A is predominant in UPEC strains followed by group B2 and lastly D. The predominance of phylogroup A E. coli has been also reported in China, 39 Russia 40 and Iran. 41 It has been suggested that phylogroup A could be pathogenic as other E. coli phylogroups as it possess the virulence genes as other pathogenic phylogroups.…”
Section: Discussionsupporting
confidence: 90%
“…The predominance of phylogenetic group A in UPEC isolates which is usually associated with commensal strains suggesting that the gastrointestinal tract is the main source of strains that colonize the urinary tract [32, 33]. The distribution of virulence genes and phylogenetic types varies among different countries, for example, group A was the most prevalent in Russia [34], and also in China [35] in UPEC, so our findings can be explained by geographical variation.…”
Section: Discussionmentioning
confidence: 84%